Impact of Climate Change on the Livelihoods of Learners from Child-Headed Families at a Selected Secondary School, Zimbabwe - Makamure, Annamaria; Chikuvadze, Pinias; Makuvire, Claretah (Journal of Educational Research and Practice, 2025)
This study aimed to explore the impact of climate change on the livelihoods of secondary school learners from child-headed families. Anchored in a qualitative approach, data were collected through document analysis and in-depth interviews. Purposive sampling ensured the inclusion of 15 learners from child-headed families and 5 class teachers to achieve data triangulation. Thematic analysis of the findings revealed that participants perceived climate change as the long-term alteration of global weather patterns caused by human activities and natural factors. Climate change exacerbated food insecurity among these learners due to increasing droughts and extreme weather events disrupting agriculture. Participants reported emotional and psychological stress linked to climate-related challenges but highlighted adaptive strategies such as sustainable agricultural practices, community support, and participation in resilience-building educational programmes. The findings concluded that climate change significantly disrupts livelihoods by intensifying food insecurity, water scarcity, and economic hardships, limiting educational opportunities and overall well-being for learners in child-headed households. To address these issues, the study recommends promoting food security programmes and providing educational opportunities focused on climate adaptation to enhance resilience among affected learners. This study underscores the urgent need for targeted interventions to mitigate the adverse impacts of climate change on vulnerable populations.